1997
DOI: 10.1002/ana.410410407
|View full text |Cite
|
Sign up to set email alerts
|

Machado‐joseph disease: Clinical, molecular, and metabolic characterization in chinese kindreds

Abstract: Machado-Joseph disease, an autosomal dominant multisystem motor degeneration, has been described mainly in people of Portuguese descent. Our report documents the presence of Machado-Joseph disease in the Chinese population, based on the specific molecular marker of a CAG repeat array in the 3' end of the MJD gene. We screened 21 Chinese families with dominant spinocerebellar ataxia. The results showed that Machado-Joseph disease with CAG expansion accounted for 52% of families with autosomal dominant cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 32 publications
2
54
1
Order By: Relevance
“…These lesions, newly recognized by polyglutamine immunohistochemistry, may be responsible for the cerebral cortical dysfunctions in SCA3 patients. Consistent with the results of this pathological study, the regional cerebral glucose metabolism or perfusion in SCA3, studied with PET or SPECT, was found to be significantly decreased in the entire cerebral cortex [41], occipital cortex [42], frontal, temporal and parietal lobes [43] aswell as in the cerebellar hemispheres, vermis, and brain stem. Murata et al [44] found similar results using MRI; not only were the widths of the superior cerebellar peduncles reduced and the transverse diameters of the globus pallidus and pons diminished, but the frontal and temporal lobes were also atrophied.…”
Section: Spinocerebellar Ataxia Type 3 (Machado-joseph Disease)supporting
confidence: 70%
“…These lesions, newly recognized by polyglutamine immunohistochemistry, may be responsible for the cerebral cortical dysfunctions in SCA3 patients. Consistent with the results of this pathological study, the regional cerebral glucose metabolism or perfusion in SCA3, studied with PET or SPECT, was found to be significantly decreased in the entire cerebral cortex [41], occipital cortex [42], frontal, temporal and parietal lobes [43] aswell as in the cerebellar hemispheres, vermis, and brain stem. Murata et al [44] found similar results using MRI; not only were the widths of the superior cerebellar peduncles reduced and the transverse diameters of the globus pallidus and pons diminished, but the frontal and temporal lobes were also atrophied.…”
Section: Spinocerebellar Ataxia Type 3 (Machado-joseph Disease)supporting
confidence: 70%
“…Normal variation in size of the CAG repeats of SCA1 and MJD genes has been reported in a few surveys (Rubinsztein et al, 1995;Watkins et al, 1995;Limprasert et al, 1996;Richards et al, 1996;Jodice et al, 1997;Limprasert et al, 1997;Takano et al, 1998), as well as in comparative studies carried out in affected and control groups (Dürr et al, 1996;Goldfarb et al, 1996;Maruyama et al, 1996;Matsumura et al, 1996;Hsieh et al,1997;Soong et al, 1997;Zhou et al, 1997;Lokkegaard et al, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…SCA3 [11,28,29] and SCA6 [31] have previously been studied by us with PET using 2-[fluorine 18]-fluoro-2-deoxy-D-glucose (FDG). The aim of this study was to elucidate the regional patterns of cerebral hypometabolism in three genetically defined subtypes of SCA: SCA2, SCA3, and SCA6.…”
mentioning
confidence: 99%